Cognitively Accessible Academic Lessons for Students With Intellectual Disabilities Using the iPad. Issue 4 (December 2017) - Gunderson, Jamie Linn; Higgins, Kyle; Morgan, Joseph John; Tandy, Richard; Brown, Monica R.
The purpose of this study was to improve access to general education curricula, through the use of an iPad, for students with intellectual disabilities (IDs). The participants were 72 students (kindergarten through eighth grade) identified as having an ID. During the 6-week study, the 41 students in the experimental iPad group received academic instruction and completed work via the iPad, while the 31 students in the control group received the same instruction via paper-and-pencil materials. Data were compared to determine the effects of the intervention on the academic content knowledge, work completion, and teacher perceptions of the engagement of students with IDs. Student perceptions concerning the use of the iPad as a learning tool were collected and evaluated. Analyses indicate that academic student achievement increased with both the iPad and traditional teaching methods and that performance was maintained. Additionally, the iPad usage had a significant effect on the work completion and engagement of students with IDs as indicated by work completion data and teacher perceptions of engagement. Moreover, students participating in the study responded favorably about using the iPad. Implications from these findings indicate that the iPad may be an effective learning tool for students with IDs.